Metabolic derangement in polycystic kidney disease mouse models is ameliorated by mitochondrial-targeted antioxidants - Nastaran Daneshgar; Andrew W. Baguley; Peir-In Liang; Fei Wu; Yi Chu; Michael T. Kinter; Gloria A. Benavides; Michelle S. Johnson; Victor Darley-Usmar; Jianhua Zhang; Kung-Sik Chan; Dao-Fu Dai (Communications Biology, 2021)
Daneshgar et al. investigated the role of mitochondrial dysfunction in ADPKD and mitochondria protective agents as potential therapeutics. The authors reported decreased mitochondrial complex activity and downregulation of mitochondrial and metabolic proteins in ADPKD, and proposed mCAT overexpression or SS31 treatment to slow cystogenesis.